Pedostratigraphy of aeolian deposition near the Yunxian Man site on the Hanjiang River terraces, Yunxian Basin, central China. (2nd May 2016) - Sun, Xuefeng; Li, Yinghua; Feng, Xiaobo; Lu, Chengqiu; Lu, Huayu; Yi, Shuangwen; Wang, Shejiang; Wu, Shuang-Ye
Abstract: Since 2010, we have found stone artifacts at the Houfang and Dishuiyan loess sections on the second terrace of the Hanjiang River and the Wolonggang thick natural loess section on the fifth terrace of the same river near the Xuetangliangzi site. We dated Dishuiyan and Houfang loess sections by optically stimulated luminescence (OSL) and thermally transferred OSL (TT-OSL) methods respectively. Dating results showed that the loess–paleosol deposited on the second Hanjiang River terrace as L1, S1, L2, and S2 in sequence. We dated the Wolonggang loess section by high-resolution paleomagnetostratigraphic analyses. The Jaramillo subchron was found at this section. Correlating with the central Loess Plateau, we recognized the continuous loess–paleosol sequence from L9 to L15. Investigations showed that loess was continuously deposited on the terraces of the Hanjiang River at Yunxian Basin since at least 1200 ka.